Penerapan ClassPoint dalam Meningkatkan Hasil Belajar Grammar Mahasiswa Baru Universitas PGRI Ronggolawe Tuban Tahun Akademik 2024 - Wardhono, Agus (Inovasi: Jurnal Diklat Keagamaan, 2024)
This study intends to explore the effectiveness of ClassPoint as one of  learning tools and the practical aspects of its implementation to improvre grammatical competence of freshmen students. The objective of this study is   It utilizes Classroom Action Research (CAR) design. The research sample consists of 15 first-year students who are currently registered in the odd semester of the 2023/2024 academic year. Data collection methods include interview and observation by using surveys (Likert Scale), with the latter two conducted using ClassPoint and iSpring interfaces, respectively. The result of the study shows that the implementation of ClassPoint 2 as a learning tool for Basic English grammar has shown promising results. The study demonstrates a significant improvement in student performance from the first cycle to the second cycle, with the percentage of students achieving the minimum passing criteria increasing from 45.15% to 80.64%. The students also believe it can improve learning outcomes compared to traditional methods. It shows that the implementation of ClassPoint can improve Basic English Grammar’s performance of the Freshmen Students at UNIROW Tuban.